KANDOUSHI (INTERJEKSI) DALAM KOMIK KOCCHI MUITE MIIKO VOL.1 KARYA ONO ERIKO - FITRIANI, DWI NUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Kata Kunci: Kandoushi, Kandou, Yobikake, Outou, Aisatsugo. Language is the instrument of communication which is used by people to distribute their feeling and ideas. In Jappanese called kandoushi. Kandoushi arewords use to express many feel like disappointed, anger, happy, and sad. Thewriter analyze about kandoushi in the source of Comic Kocchi Muite Miiko Vol.1. This research used kualitative descriptive research to analyze ofkandoushi. Result of the research show than in the comic Kocchi Muite MiikoVol.1 There are four kinds of kandoushi like kandou, yobikake, outou, andaisatsugo. The type of kandoushi divide inti ninety part, such as are, he, iinee, ha, are, mo, ano, eeto, aa, ee, aa, ng, o, aa, he, sorya, ara, wa, haa, and wan.Yobikake just only one, that is  mo. Outou divide into four such as un, hai, iie and oi. Aisatsugo divide into nine such as ohayou, arigatou, baibai, ashitane, rasshai, douzo, itadakimasu, tadaima, and okaeri. From this research the writer concludes that there are four kinds of kandoushi which all of those have different meaning shows different expression. For other research, the writer hopes he or she can compare kandoushi in Japan andIndonesia uses source from two countries until find the same and the different of those.